Sistema de avaliação para mensurar a qualidade do telejornalismo: uma proposta de análise aplicada à TV Verdes Mares - Vasconcelos, Maria Bernadeth de Oliveira (2024)
This work aims to analyze the quality level of news programs on TV Verdes Mares, affiliated with Globo in Ceará. Since 2018, the broadcaster has experienced several changes in content production routines and in the way news is treated and expressed, such as the use of informal speeches and humorous tones in an attempt to attract public participation through infotainment. Based on the reflections brought by theorists who discuss quality and its links with television journalism, we relate two processes linked to TV Verdes Mares' television journalism with dimensions of quality: the coverage process associated with regionality manifested by the scope of coverage of reality and participation of the audience, as well as the management of content linked to the diversity of sources, themes, formats and level of public interest. We developed a measurement system, entitled the Telejournalistic Quality Indicators Applicability Test (TAIQT), aimed at analyzing proximity subcriteria (such as coverage of reality based on five classifications: local, regional, state coverage; level of participation of the audience in the collaborative production of newspapers) and diversity of sources (Schmitz, 2011), themes, formats (Boaventura, 2020) and content of public interest (Nogueira, 2017), as well as the content of surveillance (Sartor, 2018), in addition the type of approach to content based on infotainment. The results reveal inequality in content in relation to themes (greater dominance of topics in the area of public safety, traffic and health), formats (excessive use of live entries with “neutral” backgrounds, which disassociate the presence of the reporter in places or moments of an event) and in the polarity of sources. In the regionality dimension, local news had greater dominance, with virtual sources participating in collaborative production. The content of the complaint had few records, as the presence of reporters in the field proved to be little explored, also influencing the frequent use of “pending” or “moving” news that is still undefined, interfering with the content of public interest in contents. It is clear that this practice highlights the precariousness of resources to offer new perspectives and innovations in content production based on the dimensions of regionality and diversity.